Obturator prostheses versus free tissue transfers: a systematic review of the optimal approach to improving the quality of life for patients with maxillary defects - Brandão, Thais Bianca; Vechiato Filho, Aljomar José; Batista, Victor Eduardo de Souza [UNESP]; Oliveira, Maria Cecília Querido de; Santos-Silva, Alan Roger (Elsevier B. V., 2015)
Patient perspectives on the treatment options for maxillary defects, which include free tissue transfers or obturator prostheses, may help eliminate current uncertainty as to the best choice of treatment plan. The purpose of this systematic review was to evaluate the quality of life (QoL) of patients with maxillary defects who had undergone restoration with obturator prostheses and/or free tissue transfers. A systematic search of Medline/PubMed and Web of Science databases for articles published before April 2015 was performed by 2 independent reviewers. A manual search of articles published from January 2005 to March 2015 was also conducted. Studies published in English that evaluated the QoL in patients with head and neck cancers were included. The Cohen kappa method was used to calculate inter-reviewer agreement. Ten studies were included. The University of Washington Head and Neck Questionnaire (UW-QOL) was most commonly used to measure QoL. The majority of maxillary defects were Class IIa-b. Two studies reported that the global QoL for patients with obturator prostheses is equivalent to or even better than that of other chronic disease populations. One study revealed no significant difference in QoL when the 2 treatment options were compared. The limited data indicate that the QoL of patients treated with obturator prostheses and that of patients free of tumors is similar. Well-designed clinical studies are necessary to draw definitive conclusions about how obturator prostheses compare with free tissue transfers in terms of affecting patient QoL.